Transmisi Data Citra pada Sistem Komunikasi Nirkabel dengan Teknik MIMO - Damar Widjaja; Yakobus Agung Purwanto (KONSTELASI: Konvergensi Teknologi dan Sistem Informasi, 2021)
Wireless data communication systems using Multiple Input Multiple Output (MIMO) technique in its transmission system has been well developed to solve many transmission media problems. This study aims to analyse the performance of MIMO 2x2 and MIMO 4x4 using image data. Encoding technique that is used in this study is Space Time Block Coding (STBC) by Alamouti. The result of this study shows that wireless communication system using MIMO technique is able to recover the image data on the receiver side the same as the image data on the transmitter side when SNR = 6.5dB for MIMO 2x2 and SNR = 4.5dB for MIMO 4x4.